2012
DOI: 10.1002/clen.201100693
|View full text |Cite|
|
Sign up to set email alerts
|

Biodegradation of Herbicide Propanil and Its Subproduct 3,4‐Dichloroaniline in Water

Abstract: The rational use of pesticides generates an impact which is normally reversed and eliminated by the environment itself. However, the indiscriminate use of pesticides makes its natural degradation rhythm difficult, prolonging their presence in the soil for a great deal of time. Aiming towards a decrease in the environmental impact of pesticides, soil microorganisms capable of degrading pesticides, such as propanil, were investigated. An Enterobacter cloacae strain, isolated from rice field soil, was exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The acetate buffered QuEChERS method was adequate for the extraction of the selected compounds. The method permitted the determination of polar compounds, including the metabolite 3,4‐dichloroaniline (3,4‐DCA) originated by the herbicides propanil, diuron, and linuron . It is well known that the presence of metabolites of pesticides in food is a concern and can affect human health .…”
Section: Resultsmentioning
confidence: 99%
“…The acetate buffered QuEChERS method was adequate for the extraction of the selected compounds. The method permitted the determination of polar compounds, including the metabolite 3,4‐dichloroaniline (3,4‐DCA) originated by the herbicides propanil, diuron, and linuron . It is well known that the presence of metabolites of pesticides in food is a concern and can affect human health .…”
Section: Resultsmentioning
confidence: 99%
“…Different compositions of mobile phase containing acetonitrile, methanol, and water (pH 3) were tested according (ROEHRS et al, 2012). The mobile phase was composed with acetonitrile/methanol/ultrapure water in pH 3 (aqueous phosphoric acid solution (1:1, v/v) in the ratio of 27:27:46% with a flow rate of 0.9 mL/min at time 0-20 min, and 30:30:40% with flow rate 1.2 mL/min at time 20-35 min.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The result in Tables 2 and 3 suggest that the concentrations of 3,4-DCA in both blood cockle and sediment were lower compared to the parent material of diuron. 3,4-DCA has high solubility in various discharge paths, mainly in the water and soil, and passes through the biodegradation process either by bacteria or fungi [43][44][45][46][47]. Another study revealed that algae has the potential to remove 3,4-DCA in the aquatic environment.…”
Section: 4-dcamentioning
confidence: 99%